Adsorption and desorption of ammonium by maple wood biochar as a function of oxidation and pH. (November 2015) - Wang, Bing; Lehmann, Johannes; Hanley, Kelly; Hestrin, Rachel; Enders, Akio
Highlights: Oxidizing biochars at their lowered pH did not increase ammonium adsorption. Adsorption was not fully reversible in aqueous solution. Extraction with KCl extracts nearly all adsorbed ammonium. Unrecovered ammonium was negligible at high oxidation, but increased at high pH. Unrecovered ammonium has likely been volatilized as ammonia. Abstract: The objective of this work was to investigate the retention mechanisms of ammonium in aqueous solution by using progressively oxidized maple wood biochar at different pH values. Hydrogen peroxide was used to oxidize the biochar to pH values ranging from 8.1 to 3.7, with one set being adjusted to a pH of 7 afterwards. Oxidizing the biochars at their lowered pH did not increase their ability to adsorb ammonium. However, neutralizing the oxygen-containing surface functional groups on oxidized biochar to pH 7 increased ammonia adsorption two to three-fold for biochars originally at pH 3.7–6, but did not change adsorption of biochars oxidized to pH 7 and above. The adsorption characteristics of ammonium are well described by the Freundlich equation. Adsorption was not fully reversible in water, and less than 27% ammonium was desorbed in water in two consecutive steps than previously adsorbed, for biochars with a pH below 7, irrespective of oxidation. Recovery using an extraction with 2 M KCl increased from 34% to 99% of ammonium undesorbed by both preceding water extractions with increasing oxidation, largely irrespective of pH adjustment. Unrecovered ammonium in all extractions and residual biochar was negligible at high oxidation, but increased to 39% of initially adsorbed amounts at high pH, likely due to low amounts adsorbed and possible ammonia volatilization losses.